TEOLOGI PENYEMBAHAN DALAM KITAB MAZMUR: RELASI ALLAH DAN UMAT DALAM IBADAH YANG HOLISTIK - Eirene Victoria Sele Barail; Resa Junias (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
This article aims to analyze the theology of worship in the Book of Psalms by emphasizing the relationship between God and the people from a holistic perspective of worship. This research uses a qualitative-descriptive approach through a literature review with a hermeneutical analysis of the Psalms and Old Testament theological literature. The results show that worship in the Book of Psalms is not only centered on praise and thanksgiving, but also encompasses lamentation, trust, obedience, and the ethical dimensions of the people's lives. Lexical analysis of Hebrew terms such as שָׁכַח (shachah),עֲבָד (ʿabad), הָלַל (halal), יָדָה (yadah), זָמַר (zamar), and בָּרַךְ (barak) demonstrates that worship is holistic, involving physical, verbal, musical, and relational aspects. Furthermore, the concept of covenant (berît) and God's ḥesed is the primary foundation of God's relationship with His people. Research findings confirm that the psalms of lament hold a fundamental place in the theology of worship because they maintain the people's relationship with God amidst suffering.